Rekayasa Solar Distilator untuk Memperbaiki Kualitas Fe, Mn Dan Kekeruhan Serta Kuantitas Air dalam Upaya Penyediaan Air Minum - Rochmad Bayu Purnomoaji; Tuntas Bagyono; Purwanto Purwanto (Poltekkes Kemenkes Yogyakarta, 2013)
Water which are used for drinking have to fulfill some requirements, both qualitatively and quanti-tatively. One of the qualitative requirements is the water must have tolerable iron and mangane-se concentration, as well as the turbidity. To gain the high quality of drinking water, support from appropriate technology is frequently required. Solar distillator, a technology used to distilate wa-ter by using solar energy, can be applied for reducing dengan concentration of those parame-ters. The purpose of this research was to ascertain the effect of the distillator towards the reduct-ion of the three parameters, as well as the output volume of the processed water gained from the device’s slope of 10º and 20º. Type of the research used was pre-experimental one with one group pre test post test design approach. There were 15 replications, and the examination of the iron and manganese concentration were held in the laboratory of Environmental Health Depart-ment fo Yogyakarta Polytechnic of Health, meanwhile for the turbidity, it was referred to the labo-ratory of Tirta Dharma Water Company in Sleman. The data were analysed by using Wilcoxon and Mann Whitney statistical tests at 95 % confidence level, and the results showed that the reduction of the all parameters’ concentration were significant (all p values were under 0,001), and the water volume yielded from the two device’s slopes were also significantly different (p va-lue < 0,001), i.e. in average, from 10º was 946 ml/ m2/day and from 20º was 1866 ml/m2/day.